2012
DOI: 10.1002/srin.201100233
|View full text |Cite
|
Sign up to set email alerts
|

A Thermodynamic Model for Prediction of Iron Oxide Activity in Some FeO‐Containing Slag Systems

Abstract: A thermodynamic model for calculating the mass action concentrations of structural units in CaO-SiO 2 -MgO-FeO-MnO-Al 2 O 3 -CaF 2 slags, i.e., the IMCT-N i model, has been developed based on the ion and molecule coexistence theory (IMCT). The calculated comprehensive mass action concentration of iron oxides N Fe t O has been compared with the reported activity of iron oxide a Fe t O in 14 FeO-containing slag systems from literatures. The good agreement between the calculated N Fe t O and reported a Fe t O ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 59 publications
(93 citation statements)
references
References 44 publications
0
93
0
Order By: Relevance
“…Thus, activity a R;Fe of Fe as solvent in metal film relative to pure matter as a standard state as well as activity coefficient f %;i of [O] and [P] in metal film can be considered to be close to 1.0. Moreover, many studies had indicated [6][7][8]27,28] that activity a Fe t O of Fe t O in metallurgical slags can precisely be described by the defined comprehensive mass action concentration N Fe t O of iron oxides based on the MCT. [5][6][7][8][22][23][24][25][26][27][28][29][30][31][32] …”
Section: Cao Sio 2 Mgo Feo Fementioning
confidence: 99%
See 2 more Smart Citations
“…Thus, activity a R;Fe of Fe as solvent in metal film relative to pure matter as a standard state as well as activity coefficient f %;i of [O] and [P] in metal film can be considered to be close to 1.0. Moreover, many studies had indicated [6][7][8]27,28] that activity a Fe t O of Fe t O in metallurgical slags can precisely be described by the defined comprehensive mass action concentration N Fe t O of iron oxides based on the MCT. [5][6][7][8][22][23][24][25][26][27][28][29][30][31][32] …”
Section: Cao Sio 2 Mgo Feo Fementioning
confidence: 99%
“…The calculated [22] values of the mass action concentration N P 2 O 5 of P 2 O 5 in the CaO-based slags by the IMCT [5][6][7][8][22][23][24][25][26][27][28][29][30][31][32] are also tabulated in Table I. Comparison between the calculated [ Figure 1 [7c] are greater than the calculated [22] results of N P 2 O 5 about 100 times as shown in Figure 1 [9c] are much smaller than the calculated [22] results of N P 2 O 5 about 10 10 times as illustrated in Figure 1 Figure 1(c).…”
Section: In Cao-based Slagsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a general method for developing the prediction model of k P or L P with ideal accuracy from the reported models has been suggested or provided through revising the collected models for the assigned slags equilibrated with molten steel or hot metals. In addition, the developed L P model [84] based on the ion and molecule coexistence theory (IMCT) [81][82][83][84][85][86][87][88][89][90][91][92][93][94] for slags, i.e., the IMCT-L P model, [84] for hot metal dephosphorization by CaObased slags has also been assessed through comparison with the predicted results by the revised models from the literature.…”
Section: ½4mentioning
confidence: 99%
“…6, the activity of FeO for that mole fraction is in the range of 0.01-0.03. In fact, many scholars 4,16,21,[24][25][26] have investigated the activity of FeO in slag, and most activity values were in the range of 0.01-0.03.…”
Section: Fe-o Equilibrium At Slag-steel Interfacementioning
confidence: 99%